The minimum flow of rivers in the basin of the river Buktyrma (Journal of Geography and Environmental Management, 2018)
The main regularities of the formation of the minimum river runoff in the pool of the river Buktyrmawere determined in the conditions of the Kazakh Altai. The work was carried out with the use ofavailable materials of long-term observations of average monthly expenses and daily minimum waterflow rates of the study area main rivers within the hydrological network of RSE “Kazhidromet” throughthe period including 2014. The analysis and reconstruction of the series of observations was carriedout, the calculated representative period of 1933-2014 was chosen. The quantitative characteristicsof the minimum monthly and daily water outlays for summer-autumn and winter low water averageshave been determined for a long-term period. The errors in the calculation of the norm and the coefficientof variation of the minimum runoff were investigated. Calculation errors are within the allowedvalues. The average error in calculating the minimum flow rate was ± 4,0 %, and the coefficient ofvariation Cv – ± 3,1 %.The minimum monthly and minimum daily expenses of the summer-autumn and winter inter-renniesof various security have been received. On the basis of the analysis of the course of data on the minimumrunoff averaged over rolling decades for the main rivers of the pool of Buktyrma river during the last 40-year period (1974-2014), trends were revealed and regression equations used for long-term forecastingof changes in the minimum monthly runoff of the summer-autumn and winter low water until 2020 and 2030 were obtained. There have also been given the forecast changes in the minimum monthly runoff ofthe main rivers in the basin of the river Buktyrma.